On some properties of quadratic stochastic processes - Nikodem, Kazimierz (Annales Mathematicae Silesianae, 1990)
In this paper we prove that every measurable quadratic stochastic process X : RN×Ω→R is continuous and has the form X(x,·) = Σi,j=1NxixjYi,j(·) (a.e.), where x = (x1,...,xN)∈RN and Yi,j: Ω→R are random variables. Moreover, we give a proof of the stability of the quadratic stochastic processes.